One‐Dimensional Looped Chain and Two‐Dimensional Square Grid Coordination Polymers: Encapsulation of Bis(1, 2, 4‐Triazole)‐trans‐cyclohexane into the Voids. Issue 5 (27th November 2018) - Adarsh, Nayarassery N.; Dîrtu, Marinela M.; Guionneau, Philippe; Devlin, Eamonn; Sanakis, Yiannis; Howard, Judith A. K.; Chattopadhyay, Basab; Garcia, Yann
Abstract : Two new coordination polymers [Cu(btzx)2 (MeOH)2 ](NO3 )2 (1 ) and [Cu(btrcy)2 (H2 O)2 ](ClO4 )2 · btrcy (2 ) have been synthesized by reacting two bis‐triazole/tetrazole‐ligands namely m ‐xylylene‐bis(tetrazole) (btzx) and bis(1, 2, 4‐triazole)‐ trans ‐cyclohexane (btrcy) with Cu(NO3 )2 and Cu(ClO4 )2 respectively in a 1:3 metal/ligand ratio. These compounds are shown to form X‐ray quality single‐crystals under different conditions, and the crystal structures have been determined by single‐crystal X‐ray diffraction (SXRD). The SXRD data analysis revealed that1 and2 are 1D looped chain and 2D‐square grid coordination polymers, respectively. More interestingly, the 2D‐square grid architecture in2 acts as an excellent host for the large guest ligand molecule btrcy, which is encapsulated within the voids of the 2D coordination polymer. Abstract : The spontaneous self‐assembly of bis‐azole ligands such as m ‐xylylene‐bis(tetrazole) (btzx), and bis(1, 2, 4‐triazole)‐ trans ‐cyclohexane (btrcy) with Cu(NO3 )2 and Cu(ClO4 )2 resulted in a 1D looped chain (1 ) and a 2D square grid (2 ), respectively. The grid architecture in2 acts as an excellent host for the large guest ligand molecule btrcy, which was found encapsulated within the voids of the 2D coordination polymer.